The response of Boer goats to natural and deliberate gastrointestinal nematode infection - Basripuzi Nurul Hayyan Hassan Basri (2019)
Gastrointestinal nematode infection is one of the major diseases affecting sheep and goats but most of the studies have focused on sheep. As a highly productive meat breed of goats, it is important to study the response of Boer breed to gastrointestinal nematode infection. The aim of this study was to investigate the interaction between Boer goats and their gastrointestinal nematodes by evaluating the phenotypic (faecal egg counts (FEC), IgA, packed cell volume (PCV), peripheral eosinophil counts and bodyweight) and parasitological (nematode number, length and index) variables following natural and deliberate co-infections that were dominated by Teladorsagia circumcincta and Haemonchus contortus, respectively.